2009
DOI: 10.1186/1749-8104-4-14
|View full text |Cite
|
Sign up to set email alerts
|

Vsx2 in the zebrafish retina: restricted lineages through derepression

Abstract: Background: The neurons in the vertebrate retina arise from multipotent retinal progenitor cells (RPCs). It is not clear, however, which progenitors are multipotent or why they are multipotent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
143
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(161 citation statements)
references
References 50 publications
16
143
2
Order By: Relevance
“…In agreement with our observations (Fig. 6F and Supplementary Table 6), microphthalmia has already been described in vsx2 loss-of-function models in both mouse and zebrafish 13,16 . Moreover, at optic cup stages, morphant retinas showed reduced cell number without exhibiting increased cell death (that is, pyknotic nuclei) or significant variation of the mitotic index ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…In agreement with our observations (Fig. 6F and Supplementary Table 6), microphthalmia has already been described in vsx2 loss-of-function models in both mouse and zebrafish 13,16 . Moreover, at optic cup stages, morphant retinas showed reduced cell number without exhibiting increased cell death (that is, pyknotic nuclei) or significant variation of the mitotic index ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 92%
“…Initial analysis of Vsx2 function described that its mutation in mice (ocular retardation, or j ) resulted in microphthalmia, and revealed its essential role in neuroepithelial proliferation and bipolar cells differentiation 13 . Similar phenotypes were also observed in human Vsx2 mutations 14 and in vsx2-depleted embryos in zebrafish 15,16 . More recent studies on early stages of eye development have shown that Vsx2 represses Mitf and hence RPE identity, thus acting as a central component of the gene regulatory network involved in the specification of the neural retina domain [17][18][19][20] .…”
supporting
confidence: 78%
See 2 more Smart Citations
“…Based on the expression pattern, a more likely candidate of an atoh7 repressor would be the Wnt/b-catenin-dependent sox2. Also, a recent study showed that vsx2, a retinal progenitor marker, is able to repress atoh7 directly (Vitorino et al, 2009). However, the exact nature of how all these different pathways interact during zebrafish retinogenesis remains to be determined.…”
Section: Wnt/b-catenin Signaling Upregulates Genes That Inhibit Neuramentioning
confidence: 99%